Pengaruh Budaya Kerja Terhadap Kinerja Karyawan di CV. Phenominca Radharani - Lorensa, Kadek Risal; Citrawati, Luh Putu; Kusumarini, Indah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2023)
This study aims to determine the effect of work culture (X) on employee performance (Y) at CV. Phenominca Radharani. Data were collected through questionnaires and interviews. Data were analyzed by simple linear regression with a population of 30 people. The results of data analysis show that the variable (X) is positively and partially significant to the variable (Y). This is evidenced by the value of t arithmetic 9.471 > t table 1.701 and a significance of 0.000 <0.05. Variable (X) contributed 76.2% to variable (Y). While the remaining 23.8% is influenced by other factors. The variable (X) on the “individual orientation” indicator is the indicator that gets the lowest value (3.37). This shows that employees have not been able to meet the targets set by the company. While the